Meteorological data from Almbergasjön, littoral - Abisko Scientific Research Station (Swedish Polar Research Secretariat, 2025)
Automatic weather station data from locations within the distributed Swedish research infrastructure SITES. Check preview or file for the specific parameters included at this location. Data has been quality controlled and cleaned from outliers and other events producing unrealistic data. Gaps have not been filled.
Abisko Scientific Research Station (2025). Meteorological data from Almbergasjön, littoral, 2023 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/iB_rzm-CZ7NUiXRofSCgpdac
Keywords: Abisko Scientific Research Station; Atmospheric radiation; Humidity; Precipitation; Surface Winds; Time instant; Time instant; Wind direction; Wind direction; Wind speed; Wind speed; Air temperature; Air temperature; Relative humidity; Relative humidity; Air pressure; Air pressure; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap